INTERNATIONAL GRANT COOPERATION AS A TOOL FOR THE DEVELOPMENT OF PROFESSIONAL COMPETENCIES OF UNIVERSITY TEACHERS - Chmura, Milan (Педагогічна освіта: Теорія і практика. Психологія. Педагогіка., 2020)
The education and development of university teachers have its justifcation and its importance is signifcant not only in the Czech Republic but also abroad. This study provides an analysis of further professional education of university teachers in the Czech Republic and in selected European countries. Subsequently, it presents an international project with participants from the Czech Republic, Ukraine, Slovakia and Poland, which, ultimately, plays a role in the improvement of the quality of higher education.